Free basic education and quality of life for teachers in Catholic schools in the City of Goma, DRC. - Sr Daphrose Rwanyonga, (IJRDO- Journal of Educational Research, 2024)
This paper aims to evaluate the influence of free basic education on the Catholic schoolsteacher’s quality of life in the Goma town. Interviews were carried out with 267 teachers fromthe Sub-Divisions of Goma, Karisimbi I and II using a questionnaire. The findings was that 29%of teachers felt that before free access, their situation was generally “good”; 22% say their healthwas very good; 25% say that their financial situation was “good”; 28% believe that their socialsituation was “good”. After applying the free access, 25% say that their situation has, in general,become “poor”; 45% say that their financial situation has become “poor” at the same time as31% maintain that teachers’ collaboration with the authorities has also become “poor”